Analisis Soal HOTS Pada Buku Teks Kimia Kelas XI Semester Genap SMA/MA Di Kota Palangka Raya - Saragih, Agnech Gloria Putri; Sidauruk, Suandi; Meiliawati, Ruli (Jurnal Ilmiah Kanderang Tingang, 2024)
Education in general aims to improve the nation's intelligence through increasing understanding of the material obtained during the learning process. The chemistry learning process is never separated from chemistry textbooks which are used as the main learning resource that stimulates curiosity and improves students' thinking processes so as to achieve higher-order thinking skills. in accordance with the 2013 curriculum. This study aims to determine aspects of higher-order thinking skills that are developed in questions in chemistry textbooks for class XI even semester. The research method used is descriptive qualitative method. The sample in this research is a question document in a chemistry textbook for class XI even semester obtained by technique purposive sampling. The research instrument used was a question analysis sheet based on HOTS aspects according to Brookhart. The results of this study indicate that the HOTS aspects developed in the questions on chemistry textbooks for class XI even semester SMA/MA in Palangka Raya only have a percentage of 30.3% consisting of 17.8% analyzing aspects, 1.1% creating aspects, aspects of reasoning and logic 3.4%%, aspects of problem solving 7.4% and aspects of creativity and creative thinking 0.6%, while aspects of evaluating and aspects of decision making do not contain any questions in the textbooks analyzed, thus it is concluded that the questions The HOTS being developed is still dominated by questions that do aspects Non-HOTS according to Brookhart.